THE IMPLEMENTATION OF TRAINING AND EDUCATION PROGRAM FOR THE HEADMASTER CANDIDATES AT EDUCATION QUALITY GUARANTY INSTITUTION (LPMP) LAMPUNG - Fardarita; Ahmad (JISAE: Journal of Indonesian Student Assessment and Evaluation, 2020)
This research was aimed at investigating the reaction, learning achievement, behavior changing, and the effect of training and education program for headmaster candidates by paying attention on institutional, instructional, and behavioral dimension. The research was conducted at the Education Quality Guaranty Institution Lampung. The evaluative qualitative research was applied in this research using blended model of evaluative training model of the Four Levels and the three dimensions cube model. The data was collected by giving questionnaire, observation, interview, documentation, and headmaster candidates’ test results. The result of the research revealed that the purpose of the program was formulated based on the participants’ need, considering the clear qualification of the purpose formulation and the outcome could be observed, the program design described the continuous application strategy dealt with the competence structure, the realization of time, the training and education needed to be improved especially in the use of method, time, management, and the quality of the consumption, the participants’ behavior changing after going back to their working place, the result of the training and education program impacted very much in increasing the school quality, and the appointment of the headmasters considered their competence. As the result of the evaluation, it can be concluded that the headmaster candidates training and education program is categorized good and recommended to be continued with some improvements.